Beyond uncertainty: A broader scope for "incentive hope" mechanisms and its implications. (2019) - Linkovski, Omer; Weinbach, Noam; Edelman, Shimon; Feldman, Marcus W.; Lotem, Arnon; Kolodny, Oren
Abstract: We propose that food-related uncertainty is but one of multiple cues that predicts harsh conditions and may activate "incentive hope." An evolutionarily adaptive response to these would have been to shift to a behavioral-metabolic phenotype geared toward facing hardship. In modernity, this phenotype may lead to pathologies such as obesity and hoarding. Our perspective suggests a novel therapeutic approach.